MOTIVASI, BATASAN, DAN PELUANG MANAJEMEN LABA (STUDI EMPIRIS PADA INDUSTRI PERBANKAN YANG TERDAFTAR DI BURSA EFEK JAKARTA) - Rahmawati Rahmawati (Faculty of Economics and Business, Universitas Gadjah Mada, 2008)
The purposes of this research are: (1) to test the relationship between information asymmetry, audit quality (constraints on earnings management) and earnings management, and (2) to test the influence banking regulation, profitability (incentives to manage earnings) to earnings management. The regulation mentioned in this research is banking regulation which directly and indirectly influences company earnings. They are carefulness regulation and health level regulation. The main motivation of earnings management by the banking industry is to fulfill the regulation. Result of this research can benefit to theory development, accounting standard organizer, regulator (Bank Indonesia), and also investor. This research data are collected from ICMD (Indonesian Capital Market Directory) and/or annual report company which are provided by the Capital Market Reference Center (PRPM) of Indonesia Stock Exchange (BEI) and also financial statement of public banking companies published by Indonesia Banking Directory. Population of this research is all public bank exists at Indonesian in the year 1999 until 2004 which enlist in BEI. Purposive sampling method was used to collecting data, and 120 observations are collected. The existence of earnings management in banking industries is indicated by the mean of discretionary accrual not equal to zero (negative). The discretionary accrual as a proxy to earnings management is influenced by the health level banking regulation. Banks whose health score decrease make reducing earnings to can increase their balance of productive assets loss allowance (PPAP). Information asymmetry moderates relationship between banking regulation of carefulness and earnings management. This conclusion support the research of Rahmawati (2006), Beaver and Engel (1996), Wahlen (1994), Moyer (1990), Niswander and Swanson (2000). Audit quality do not influenced earnings management in this research, because this research uses audit quality proxy with size of public accountant firm. Profitability influences earnings management at significant 10%.